Iowa CBC reporting form, Marshalltown, December 21, 1985 - Savage, Edet al (1985)
Checklist dated December 21, 1985 compiled by Ed Savage. A list of birds sighted by Savage and twenty-five others around Marshalltown. A total of 42 species and 3,835 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed